SUSTAINABLE WASTE MANAGEMENT STRATEGIES IN SOUTH KOREA AND UZBEKISTAN - Sherquziyeva , Iroda; Shukurullayeva , Maftuna; Goyibnazorova , Shahnoza (Scientific practical conference, 2025)
This article presents important information, issues, and solutions regarding waste management in South Korea and Uzbekistan. Currently, South Korea is one of the most developed countries in the world. Despite numerous achievements, it faces challenges in several areas, such as waste management, similar to our country. We examine the similarities and issues between the two countries and propose solutions for them.